Funding growth in bank-based and market-based financial systems : evidence from firm level data - Demirgüç-Kunt, Asli, 1961- 1961- (Policy research working paper, 2000)
How the relative development of a country's stock market and banking system affects firms' growth is closely tied to how well developed the country's contracting environment is. How differences in the contracting environment affect the relative development of the stock market or banking system may have implications for which firms and which projects get financing